Chemical Composition and Cytotoxic and Antibacterial Activities of the Essential Oil of Aloysia citriodora Palau Grown in Morocco - Oukerrou, Moulay Ali (Adv Pharmacol Sci, 2017)
The aim of this work is to investigate the in vitro cytotoxic and antibacterial effects of the essential oils of Aloysia citriodora Palau, harvested in different regions of Morocco. The chemical profile was established using gas chromatography-mass spectrometry analysis. The cytotoxic activity against P815, MCF7, and VERO cell lines as well as the normal human peripheral blood mononuclear cells (PBMCs) was evaluated using the MTT assay. Standard, ATCC, strains of bacteria (Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa) were cultivated in Muller Hinton media. Then, agar disc diffusion, minimum inhibitory concentrations (MICs), and minimal bactericidal concentrations (MBCs) were determined using microdilution method. The essential oils obtained were predominantly composed of β-spathulenol (15.61%), Ar-curcumene (14.15%), trans-caryophyllene oxide (14.14%), and neral (10.02%). The results of the assays showed that the cytotoxic effect of the essential oil of A. citriodora was high on P815 and moderate on MCF7 and on VERO cell lines. However, no cytotoxic effect was observed on PBMCs. On the other hand, essential oils showed a significant antimicrobial activity against both Gram-negative and Gram-positive bacteria. MICs ranged between 2.84 and 8.37 mg/ml. Essential oil of A. citriodora leaves possesses significant antibacterial effect and cytotoxic activity against tumor cell lines.